Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/anie.200700247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mixing of Metal Cations on the Topology of Metal Oxide Networks

Abstract: Four distinct phases were isolated by adjusting the Co/Ni ratio in the hydrothermal system CoCl2/NiCl2/succinic acid/KOH/H2O. In addition to clarifying the relationships between known hybrid inorganic–organic materials 1, 2, and 4, [M7(OH)2(H2O)2(C4H4O4)6]⋅3.5 H2O (3), a hybrid metal oxide with a rare three‐dimensional metal–oxygen–metal framework, was discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…For MOCNs 1-4, it is likely that subtle alterations in the binodal cubical vertices/ square-planar connectivity between the trimetallic clusters and the btec ligands resulted in differences in supramolecular environments and lowered cell symmetry to a primitive monoclinic space group for the last three. The nature (d-electron configuration) of the transition metal ions (Co II , Ni II ) herein may have a significant influence on the final connectivity, [31] whereas alkali metal ions (K + , Cs + ) seem to have only a minor effect, but act as templates. This difference most likely is due to both the inherent tendency for coordination of transition metal ions (octahedral for Co II and square-planar for Ni II ) [31] and the size of the alkali metal ions (10 3 for K + and 19 3 for Cs + ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For MOCNs 1-4, it is likely that subtle alterations in the binodal cubical vertices/ square-planar connectivity between the trimetallic clusters and the btec ligands resulted in differences in supramolecular environments and lowered cell symmetry to a primitive monoclinic space group for the last three. The nature (d-electron configuration) of the transition metal ions (Co II , Ni II ) herein may have a significant influence on the final connectivity, [31] whereas alkali metal ions (K + , Cs + ) seem to have only a minor effect, but act as templates. This difference most likely is due to both the inherent tendency for coordination of transition metal ions (octahedral for Co II and square-planar for Ni II ) [31] and the size of the alkali metal ions (10 3 for K + and 19 3 for Cs + ).…”
Section: Resultsmentioning
confidence: 99%
“…The nature (d-electron configuration) of the transition metal ions (Co II , Ni II ) herein may have a significant influence on the final connectivity, [31] whereas alkali metal ions (K + , Cs + ) seem to have only a minor effect, but act as templates. This difference most likely is due to both the inherent tendency for coordination of transition metal ions (octahedral for Co II and square-planar for Ni II ) [31] and the size of the alkali metal ions (10 3 for K + and 19 3 for Cs + ). [32] For cobalt-containing metal-organic coordination networks, a regular architecture is favored in the presence www.chemeurj.org of small potassium ions.…”
Section: Resultsmentioning
confidence: 99%
“…[23,[38][39][40][41] MM-MOFs in which two different metals are presented in acertain proportion range have been reported to be prepared using synthetic procedures common in MOF synthesis,s uch as conventional heating and solvothermal procedures. [17,[42][43][44][45][46][47][48][49] Depending on the synthesis conditions and the nature and proportion of the various metal precursors the resulting MM-MOF can be derived from the thermodynamic or kinetic control and this may influence the distribution and location of the metals. Considering the possible differences,the synthetic procedures should screen av ariety of conditions,d etermining the influence of various parameters in the final MM-MOF.…”
Section: One-pot Synthesis Of Mm-mofsusing Mixtures Of Different Metamentioning
confidence: 99%
“…5,[7][8][9] Incorporating two or more different cations or ligands into a framework allows the crystal structure, and thus the functional properties of such materials, to be tailored to particular applications. [10][11][12] It has been shown that cation doping in frameworks can lead to either the formation of solid solutions 11 or a sequence of phase transitions with changing composition, 12 similarly to purely inorganic materials. The effect, however, of mixing two ligands in a framework is less clear, especially since most compounds reported to date feature two very different ligands e.g.…”
Section: Introductionmentioning
confidence: 99%